MENTORING MANAGEMENT OF STUDENT GUARDIAN ON STUDENT LEARNING READINESS TK 'AISYIYAH BUSTANUL ATFHAL DELI SERDANG - Wastuti, Sri Ngayomi Yudha; Pratiwi, Sri Nurabdiah; Jamila, Jamila (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine and describe the management of student guardian assistance in the readiness of learning for 'Aisyiyah Bustanul Atfhal Kindergarten students. The formulation of the problem in this study is how the management of student guardian assistance as part of efforts to prepare students to receive learning in kindergarten schools. This research uses a qualitative approach with a case study research type. Data collection techniques were carried out through 3 techniques, namely observation, interviews, and documentation. Data analysis used in qualitative research uses the Miles and Huberman technique, namely data collection, data reduction, data analysis and conclusion drawing. The results showed that Student Guardian Assistance Management increased the Learning Readiness of 'Aisyiyah Bustanul Atfhal Students, where students showed 4 competencies, namely: 1) Emotional maturity sufficient to overcome daily problems, 2) Adequate social skills to interact healthily with peers, 3) Sufficient cognition to concentrate during play learning, 4) Motor skill development and self-care sufficient to participate.